2020
DOI: 10.3390/molecules25040923
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Unstable Isomers of Lucilactaene and Evaluation of Anti-Inflammatory Activity of Secondary Metabolites Produced by the Endophytic Fungus Fusarium sp. QF001 from the Roots of Scutellaria baicalensis

Abstract: The filamentous fungal pathogen Fusarium sp. causes several crop diseases. Some Fusarium sp. are endophytes that produce diverse valuable bioactive secondary metabolites. Here, extensive chemical investigation of the endophytic fungus, Fusarium sp. QF001, isolated from the inner rotten part of old roots of Scutellariae baicalensis resulted in the isolation of two new photosensitive geometrical isomers of lucilactaene (compounds 2 and 3) along with lucilactaene (6) and six other known compounds (fusarubin (1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…RK97-94 culture revealed the presence of two additional unknown peaks, 2 and 3 , that overlapped with NG391/393 peaks in UPLC analysis (Figure S4). Peak 2 exhibited a UV max at 368 nm, as well as [M – H] − 402 m / z and [M + H] + 404 m / z in ESI-MS analysis, suggesting a molecular weight of 403 Da, which has never been reported for lucilactaene analogues. , Peak 3 displayed a similar mass of NGs in ESI-MS ([M – H] − 416 m / z ) but with a different retention time (Figure S4) and different UV max (360 nm) . A literature and database search suggested a possible known hydroxylated lucilactaene derivative …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…RK97-94 culture revealed the presence of two additional unknown peaks, 2 and 3 , that overlapped with NG391/393 peaks in UPLC analysis (Figure S4). Peak 2 exhibited a UV max at 368 nm, as well as [M – H] − 402 m / z and [M + H] + 404 m / z in ESI-MS analysis, suggesting a molecular weight of 403 Da, which has never been reported for lucilactaene analogues. , Peak 3 displayed a similar mass of NGs in ESI-MS ([M – H] − 416 m / z ) but with a different retention time (Figure S4) and different UV max (360 nm) . A literature and database search suggested a possible known hydroxylated lucilactaene derivative …”
Section: Resultsmentioning
confidence: 90%
“…To this end, we proposed a reduction of the carbonyl group at C-12 to its corresponding alcohol. To verify this, compound 1 was subjected to 1D- and 2D-NMR spectroscopy (Table , Figures S7–S13), and the results were compared with previously reported data for NG391/393 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maharjan et al [134] reported isolation of nine compounds including quinones, fusarubin, ( +)-solaniol, javanicin, 9-desmethylherbarine, and pyrrole analogs; isomers of lucilactaene (59,60,61), (62), and ( 63) from roots of Scutellariae baicalensis. These isolated compounds showed potential anti-inflammatory activity by inhibiting NO production and pro-inflammatory cytokines in LPSinduced RAW 264.7 macrophage cells.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…The significance of natural compounds extracted from microorganisms has been shown in nutrition, agriculture, and healthcare sciences. 1 Numerous studies have shown that microorganisms can produce many novel metabolites, such as steroids, terpenoids, flavonoids, and alkaloids, which have conspicuous antitumor, 2,3 anti-microorganism, 4 anti-inflammatory, 5 antioxidative, 6 and sugar-reducing 7 activities. Microbial metabolites have been used extensively in medicine.…”
mentioning
confidence: 99%